Adaptive Coaching Approach to Improve Social and Physical Abilities of Children with Special Needs and Mental Retardation - Yan Indra Siregar; Ahmad Syabaruddin Ahmad Syabaruddin; Stepanus Cristian H. Siahaan; Muhammad ihsan fauzi Muhammad ihsan fauzi; Michael Ezekiel Pemerena Ginting Michael Ezekiel Pemerena Ginting; Reli Efrada Tarigan Reli Efrada Tarigan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to develop and test the effectiveness of an adaptive coaching approach in improving the social and physical abilities of children with intellectual disabilities. Children with intellectual disabilities often face obstacles in understanding verbal instructions and limitations in social interaction. Using research and development (R&D) methods, an adaptive coaching approach was designed through adaptive training modules, visual demonstrations, group activity familiarization, and integrated social interaction strategies. A trial was conducted in a special needs school with 20 purposively selected participants. The results showed that this approach was able to significantly improve motor skills (such as coordination, balance, speed) and social aspects (interaction, group participation). Teachers' and trainers' perceptions of this model were also positive. Thus, an adaptive coaching approach can be an effective strategy in inclusive physical education for children with intellectual disabilities.